An investigation into grammatical metaphor in complete ghost stories by charles dickens (Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
Grammatical Metaphor plays an important role in The Functional Grammar. This thesis aims at investigating this linguistic phenomenon in the collection Complete Ghost Stories by Charles Dickens. The study is carried out based on the theories of grammatical metaphor under the light of Functional Grammar and a combination of a variety of methods such as descriptive and analytic. The investigation focuses on analyzing grammatical metaphor of 311 samples collected from the stories in terms of ideational metaphor and interpersonal metaphor. Through finding the appearance of grammatical metaphor, this thesis suggests some ways to solve the complexity of grammatical metaphor which is aimed to help readers of the stories in particular and language learners in general to be able to understand better this phenomenon. Besides, this thesis will give some applications of grammatical metaphor to teach writing and speaking English